دور دولة قطر في فض النزاعات الإقليمية والدولية أزمة إقليم دارفور بغرب السودان نموذجا - هاجري، علي غانم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study deals with the role of Qatar in resolving regional and international conflicts, “Darfur crisis in western Sudan as a case study”. The importance of the study lies in highlighting the role of Qatar in resolving the crises in the Arab region, its experiences in resolving the conflict between the conflicting parties, such as Darfur problem, as well as the sincere desire of Qatar to resolve the crisis, which made it contributes significantly to the resolution of the conflict in Darfur within the framework of settlement, resolution, dialogue and reconciliation. The study aims at identifying the root and historical causes that led to the conflict in Darfur, discussing the negotiating theories in solving such a crisis; the negotiating method of Darfur conflict resolution and the traditional heritage in resolving conflicts in this region. Furthermore, the study focuses on the impact of Qatari-Sudanese relations, which facilitate the reconciliation between the conflicting parties, the adaptation of a new approach to the conflict resolution accompanied by reconstruction after the Doha Agreement, as well as the stands of the conflicting parties, and the international community towards the agreement. The study is divided into five chapters: The First chapter discusses the methodological framework of the study. The Second chapter explores the general information about Sudan, of which are the political, economic and social background of Sudan, the history of the Old Sudan, the history of Darfur and its conflict, the globalization of the crisis in Darfur etc. The Third chapter clarifies the theoretical framework of the research. The fourth chapter deals with the Qatari-Sudanese diplomatic relations, the role of Qatari diplomacy in resolving the Darfur crisis, the essence and content of Darfur Peace Agreement (Doha Agreement). Chapter five of the research conducts the field study, in which the Qatari diplomatic strategy of engaging all the conflicting parties in the peace agreement decision discussed as well as the Darfur Development Strategy and impact of that strategy on the success of the Agreement. Finally, the conclusion of the study reveals some findings, the most important of which are: The size of Qatari diplomatic efforts and its ability as an international mediator in gaining confidence of the warring parties, as a result of its deep and successful experiences in the various crises. The Doha Agreement was accepted by all the parties that are involved in Darfur crisis.